Intimate violence across the lifespan : interpersonal, familial, and cross-generational perspectives - Band-Winterstein, Tova (The Springer Series on Human Exceptionality, 2014)
Studies of family functioning as their members age, and of elder abuse at the hands of adult children or caregivers, are recent trends in gerontology. Yet the intersection of these two ideas-the impact of prolonged domestic abuse on elders and their families-has received scant notice. Similarly, questions are posed as to whether abusers "age out" of violence, but answers have been inconclusive. Intimate Violence across the Lifespan addresses these research gaps with a groundbreaking long-term study of why domestic abuse persists, why it replicates, how abusive relationships may be altered by the processes of aging, and how violence may be stopped. The authors' phenomenological approach to their subject makes extensive use of interviews with family members to present a detailed portrait of family violence and the changing dimensions of control and secrecy as abuser and victim age. Close attention is especially paid to the frequently marginalized experiences of adult children, and how these scenarios play out as they become partners and parents. The section on intervention depicts the multiple challenges of working with husbands, wives, and children, with guidelines for encouraging change, closure, and support. Included in the coverage: Hiding as a way of life. Cumulative losses and loss of meaning. Giving meaning to life in violence. The family's summary of its journey in violence. The tension between continuity and change. Intervention: making resilience and survival possible. Intimate Violence across the Lifespan is an essential resource for researchers, graduate students, and clinicians/professionals in varied fields, including gerontology, family, psychotherapy/counseling, social work, personality and social psychology, and public health.